2021
DOI: 10.3390/nano11071715
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Hierarchical Porous TiO2 for Enhanced Adsorption and Photocatalytic Degradation of Remazol Dye

Abstract: Three-dimensional hierarchical mesoporous structures of titanium dioxide (3D-HPT) were synthesized by self-assembly emulsion polymerization. Polymethyl methacrylate (PMMA) and pluronic 123 (P123) were used as the soft templates and co-templates for assisting the formation of hierarchical 3D porous structures. The TiO2 crystal structure, morphology, and Remazol red dye degradation were investigated. The 3D-HPT and normal three-dimensional titanium dioxide (3D-T) presented the good connection of the nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The inner framework of the three dimensionally (3D) linked macropore network effectively mitigates mass transfer resistance, rendering the PM channels conducive to the diffusion and mass transfer of macromolecular reactants between the catalyst's surface and its bulk. [14,15] The incorporation of a PM structure with a larger specific surface area, yielding more reaction-active sites, translates to heightened hydrogen production activity of the catalyst. [16] For example, Peng et al [17] confirmed that 3D ordered macroporous (3DOM) WO 3 is a highly effective photocatalytic water oxidizer because of its excellent charge transport properties and excellent light harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…The inner framework of the three dimensionally (3D) linked macropore network effectively mitigates mass transfer resistance, rendering the PM channels conducive to the diffusion and mass transfer of macromolecular reactants between the catalyst's surface and its bulk. [14,15] The incorporation of a PM structure with a larger specific surface area, yielding more reaction-active sites, translates to heightened hydrogen production activity of the catalyst. [16] For example, Peng et al [17] confirmed that 3D ordered macroporous (3DOM) WO 3 is a highly effective photocatalytic water oxidizer because of its excellent charge transport properties and excellent light harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis has emerged as a potential technology for the complete removal of most harmful chemicals and bacteria from wastewater with the wide application of metal oxide nanoparticles [ 12 , 13 ]. For example, zinc oxide (ZnO) [ 14 , 15 ], bismuth oxide (Bi 2 O 3 ) [ 16 ] and titanium dioxide (TiO 2 ) [ 17 , 18 ] have been used as photocatalysts and antimicrobial agents. However, these metal oxides can only be activated by high-energy photons (λ < 400 nm) and hence with very low solar efficiency (4–5%) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The removal of dyes from wastewater is therefore urgent. The current methods of treating dyes are adsorption [31], photodegradation [32], and advanced oxidation [33]. Of these, adsorption method is the simplest and most effective technique due to its simplicity of operation, the variety of adsorbents, and environmental friendliness [34][35][36].…”
Section: Introductionmentioning
confidence: 99%